From Marx to Warner : class and stratification under scrutiny - Tittenbrun, Jacek (Cambridge Scholars Publishing, 2017)
The book offers an in-depth analysis of several important theories of social class and stratification, both past and present. This critique is underpinned by a single, coherent analytic framework organised around the notion of ownership. This original approach allows the book to offer alternative treatments of the issues dealt with by the thinkers discussed here. The central argument here is that there are only two classical theories of social class, namely those developed by Marx and Weber, and this clear systematisation of the main attributes of approaches to class and stratification makes i.